Handbook of sampling for auditing and accounting : volume 1 - methods - Arkin, Herbert (New York : McGraw-Hill, 1963)
This volume is designed to bridge the gap between the current interest in the accounting applications of sampling theory.
Includes index
II 16/01/2019
Loans
Keywords: Sampling (Statistics); Accounting; Auditing